2013
DOI: 10.1128/aac.01257-13
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Antimicrobial Treatment Effect Estimation in Complicated Urinary Tract Infection

Abstract: bNoninferiority trial design and analyses are commonly used to establish the effectiveness of a new antimicrobial drug for treatment of serious infections such as complicated urinary tract infection (cUTI). A systematic review and meta-analysis were conducted to estimate the treatment effects of three potential active comparator drugs for the design of a noninferiority trial. The systematic review identified no placebo trials of cUTI, four clinical trials of cUTI with uncomplicated urinary tract infection as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…1,2,7,8 With the increasing prevalence of antimicrobial resistance, the treatment of cUTIs has become more challenging, leading to the need to develop new antimicrobial treatments. 9,10 There are few real-world data regarding the characteristics of patients with cUTIs, their outpatient and inpatient treatment patterns, and the costs associated with the management of cUTIs. The objectives of the present study were to describe the characteristics, treatment patterns, and total costs associated with cUTI patients who received outpatient treatment only compared with those who required emergency services or hospitalization due to presumed treatment failure after outpatient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,7,8 With the increasing prevalence of antimicrobial resistance, the treatment of cUTIs has become more challenging, leading to the need to develop new antimicrobial treatments. 9,10 There are few real-world data regarding the characteristics of patients with cUTIs, their outpatient and inpatient treatment patterns, and the costs associated with the management of cUTIs. The objectives of the present study were to describe the characteristics, treatment patterns, and total costs associated with cUTI patients who received outpatient treatment only compared with those who required emergency services or hospitalization due to presumed treatment failure after outpatient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis examined multiple cUTI trials before ASPECT-cUTI and identified microbiological eradication rates at the TOC visit in the microbiological intent-to-treat population of 81% for doripenem, 79% for levofloxacin, and 80.5% for imipenem-cilastatin, confirming that levofloxacin has a place in the armamentarium for cUTI [21]. In an era of increasing and evolving antibiotic resistance, however, decisions about clinical usefulness must be made at the local hospital and individual patient level [22].…”
Section: Discussionmentioning
confidence: 99%
“…While the placebo response rate in uSSTI should not be interpreted as the true placebo response rate in ABSSSI, we assumed that the use of this proxy for the placebo treatment response, resulting in an overestimation of the ABSSSI placebo treatment response, is a conservative approach in estimating antibacterial efficacy relative to that of placebo. Based on the uncertainty of the true placebo effect and the use of the FDA guidance, each ABSSSI treatment effect estimate is conservative, given that the overestimation of the ABSSSI placebo treatment response results in a conservative underestimation of the ABSSSI treatment effect (14,22,58). The second major finding from our study is the evidence and assessment of heterogeneity in these historical clinical trials as relevant and informative to future ABSSSI clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The placebo search was extended to include clinical trials reporting a placebo treatment response in uncomplicated skin and soft tissue infections (uSSTI) as a proxy for placebo in ABSSSI (search A2). This strategy, which comprised use of a proxy for placebo effect estimation, has been recommended in the FDA guidance for noninferiority trials and has been used for placebo treatment effect estimation for trials in complicated urinary tract infections (13,21,22). Given that historical studies published in 1937 reported relatively high response rates in the treatment of erysipelas with UV light, an additional search (search C) was conducted to identify clinical trials of nonantibacterial treatment in uSSTI and in ABSSSI (4,23,24).…”
Section: Methodsmentioning
confidence: 99%